Licensing Information System In Kesbangpol Kota Pekanbaru - Muhammad Sadar; Didik Siswanto; Susi Handayani (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2019)
The development of computer technology now enables the development of computer-based information systems, so the Community Organization (ORMAS) licensing service at the National Unity and Politics Agency (Bakesbangpol) Pekanbaru City needs support from technological developments to reduce existing problems items, namely the lack of information for ORMAS administrators who want to extend the Certification of registration Community Organization ORMAS SKT, and SKT ORMAS when registering. The purpose of this research is to Facilitate all forms of licensing at the Kesbangpol office, so that the process can be more efficient in terms of time and cost. The system that will be created is a Web-based application, the design is done using Unified Modeling Language (UML) and making the system using the PHP programming language, and using a MySQL database